"Third drug" trial: comparative study of antihypertensive agents added to treatment when blood pressure remains uncontrolled by a beta blocker plus thiazide diuretic. Issue 6411 (14th January 1984) - McAreavey, D; Ramsey, L E; Latham, L; McLaren, A D; Lorimer, A R; Reid, J L; Robertson, J I; Robertson, M P; Weir, R J
Abstract : Hydralazine, labetalol, methyldopa, minoxidil, prazosin, and placebo were compared when added by random allocation to atenolol 100 mg and bendrofluazide 5 mg daily in a series of 238 hypertensive patients inadequately controlled by the beta blocker-diuretic combination. Atenolol was withdrawn in those allocated to labetalol, and minoxidil was given only to men. The order of acceptability was: placebo, hydralazine, prazosin, methyldopa, minoxidil, labetalol. Minoxidil was more effective than the other active drugs, which had similar potency to one another. All the active agents were more effective than placebo. Hydralazine was the most generally suitable third drug, with prazosin a close second. Minoxidil was especially effective in patients with less severe hypertension but the same regimen caused fluid retention in those with more severe disease. Labetalol should probably be introduced at a low dose (150 mg daily) even when replacing full doses of a previously administered beta blocker.